The Associations of Caesarean Delivery With Risk of Wheezing Diseases and Changes of T Cells in Children - Lin, Jilei; Yuan, Shuhua; Dong, Bin; Zhang, Jing; Zhang, Lei; Wu, Jinhong; Chen, Jiande; Tang, Mingyu; Zhang, Bin; Wang, Hansong; Dai, Yuanyuan; Liu, Shijian; et al. (Frontiers in Immunology, 2021)
Objectives: This study aimed to assess the associations of caesarean delivery (CD) with risk of wheezing diseases and changes of immune cells in children. Design: The cross-sectional study was conducted between May, 2020 and April, 2021. Setting and participants: The study was conducted in Shanghai Children's Medical Center, Shanghai, China. A total of 2079 children with a mean age of 36.97±40.27 months and their guardians were included in the present study via face-to-face inquiry and physical examination by clinicians. Methods: Logistic regression was applied to estimate odds ratio (ORs) and 95% confidence intervals (CIs) for the association between CD and first episode of wheezing (FEW) or asthma. Models were adjusted for premature or full-term delivery, exclusive breastfeeding (at least 4 months) or not. Results: Among the 2079 children, 987 children (47.47%) were born by CD and 1092 (52.53%) by vaginal delivery (VD). Children delivered by caesarean had significantly lower gestational age (P<0.01) compared with those who delivered vaginally. Our results also showed that CD was related to increased risk of FEW by the age of 3(adjusted OR 1.50, 95%CI 1.06, 2.12) and increased tendency to develop asthma by the age of 4 (adjusted OR 3.16, 95%CI 1.25, 9.01). The subgroup analysis revealed that the negative effects of CD on asthma were more obvious in children without exclusive breastfeeding (adjusted OR 4.93, 95%CI 1.53, 21.96) or without postnatal smoking exposure (adjusted OR 3.58, 95%CI 1.20, 13.13). Furthermore, compared with children born through VD, a significant change of the T cells (increased proportion of CD4+ T cells and decreased number and proportion of CD8+ T cells) were observed before the age of one in the CD group. However, the changes were insignificant in children over 1 year old. Conclusions: This study showed age-dependent associations of CD with asthma and FEW in offspring. Moreover, CD appeared to have an effect on the cellular immunity in infants, the disorder of which may contribute to the development of asthma in children.